TRANSFORMASI EFISIENSI RANTAI PASOK DENGAN MODEL SCOR EVALUASI STRATEGIS PADA PT. ADN WOOD BATANG - Bhakti Novansyah; ILHAM M FIRDAUS; SAILI ROCHMAH (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
PT. ADN Wood Batang faces problems in supply chain performance, particularly in the responsiveness aspect, as indicated by delays in raw material supply, failure to achieve production targets, and delays in export product deliveries. These conditions indicate the need for a comprehensive evaluation of supply chain performance as well as system support capable of improving visibility and decision-making. This study aims to analyze the supply chain performance of PT. ADN Wood Batang using the Supply Chain Operations Reference (SCOR) model and to design a monitoring system as an improvement solution. The methods used include primary and secondary data collection, supply chain performance measurement based on the five SCOR attributes (reliability, responsiveness, adaptability, cost, and asset management), and indicator weighting using the Analytical Hierarchy Process (AHP). The results show that the company’s supply chain performance is in the moderate category, with the main weakness found in the responsiveness attribute. Based on the evaluation results, a supply chain monitoring system called SIMPLY was designed to monitor the flow of raw materials, production processes, and product distribution in an integrated manner. This system is expected to improve responsiveness, coordination among divisions, and the effectiveness of supply chain management within the company.